Anoctamin 1 induces calcium-activated chloride secretion and proliferation of renal cyst-forming epithelial cells - Buchholz, Björn; Faria, Diana; Schley, Gunnar; Schreiber, Rainer; Eckardt, Kai-Uwe; Kunzelmann, Karl (Kidney International, 2014)
Polycystic kidney diseases are characterized by multiple bilateral renal cysts that gradually enlarge and lead to a decline in renal function. Cyst enlargement is driven by transepithelial chloride secretion, stimulated by enhanced levels of cyclic adenosine monophosphate, which activates apical cystic fibrosis transmembrane conductance regulator chloride channels. However, chloride secretion by calcium-dependent chloride channels, activated through stimulation of purinergic receptors, also has a major impact. To identify the molecular basis of calcium-dependent chloride secretion in cyst expansion, we determined the role of anoctamin 1 and 6, two recently discovered calcium-activated chloride channels both of which are expressed in epithelial cells. We found that anoctamin 1, which plays a role in epithelial fluid secretion and proliferation, is strongly expressed in principal-like MDCK cells (PLCs) forming cysts within a collagen matrix, in an embryonic kidney cyst model, and in human autosomal dominant polycystic kidney disease tissue. Knockdown of anoctamin 1 but not anoctamin 6 strongly diminished the calcium-dependent chloride secretion of PLCs. Moreover, two inhibitors of anoctamin ion channels, tannic acid and a more selective inhibitor of anoctamin 1, significantly inhibited PLC cyst growth and cyst enlargement in an embryonic kidney cyst model. Knockdown of ANO1 by morpholino analogs also attenuated embryonic cyst growth. Thus, calcium-activated chloride secretion by anoctamin 1 appears to be a crucial component of renal cyst growth.
EVALuna2:3642